Reduced port laparoscopic radical nephrectomy using an umbilical zigzag skin incision for renal cell carcinoma - Kaneko, Go (Int Cancer Conf J, 2020)
Reduced port laparoscopic radical nephrectomy (RPLRN) is an equivalent approach to conventional laparoscopic radical nephrectomy (LRN). In LRN, one wound generally needs to be extended for specimen extraction; therefore, some ingenuity is needed to achieve a good cosmetic outcome. We herein describe our initial experience of RPLRN using an umbilical zigzag skin incision for renal cell carcinoma (RCC). A 64-year-old female [body mass index (BMI): 20.0 kg/m(2)] was diagnosed with right RCC, which was 35 mm in diameter (clinical T1aN0M0). Case 2: a 68-year-old male (BMI: 23.2 kg/m(2)) was diagnosed with right RCC, which was 58 mm in diameter (clinical T1bN0M1), and perinephric fat was relatively thick. The procedure was safely completed in both cases. Total operative times, pneumoperitoneal times, and estimated blood loss in Case 1 and 2 were 90 and 145 min, 49 and 90 min, and 5 and 80 ml, respectively, and the times required to construct umbilical ports and close umbilical wounds were 8 and 9 min and 33 and 46 min, respectively. In Case 1, the specimen was easily extracted without the extension of the umbilical skin incision, whereas it was extended by an additional 2 cm in Case 2. The umbilical wound was inconspicuous in both cases. RPLRN using an umbilical zigzag skin incision for RCC was safely performed without complications, and clashing between instruments was minimized. The high level of cosmesis is advantageous and an umbilical zigzag skin incision may contribute to more widespread use of RPLRN for RCC; however, further studies on long-term oncological outcomes are needed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13691-020-00426-2) contains supplementary material, which is available to authorized users.